Case reports and clinical guidelines for managing radix entomolaris - Bejoy J Thomas; A Nishad; Benin Paulaian; Jonathan Emil Sam (Wolters Kluwer Medknow Publications, 2016)
Knowledge about the external and internal anatomy of the tooth is essential for successful dental practice. Anomalies in the tooth are often encountered which poses difficulties in dental treatments. As like any other tooth, mandibular first molars are also prone for anatomic malformations. One such anatomic variation is the presence of extra root distolingually. This distolingual root is called radix entomolaris (RE). The presence of an additional root can lead to difficulties during endodontic therapy. This article is a report of two cases describing the management of the first mandibular molars with an RE and clinical guidelines for its management.